FENOMENA SOSIAL BUDAYA DALAM KAJIAN TIGA CERITA RAKYAT KALIMANTAN SELATAN (SOCIO-CULTURAL PHENOMENA IN THE STUDY OF THREE FOLK STORIES SOUTH KALIMANTAN) - Kalsum, Ummi; Rafiek, Muhammad; Cahaya, Noor (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2024)
AbstractSocio-Cultural Phenomena in The Study of Three Folk Stories South Kalimantan. Folklore in South Kalimantan is a form of literature that is passed down from generation to generation by word of mouth. This research aims to describe the socio-cultural reality of South Kalimantan folklore with a sociological study of three folktales, namely: Rajang Waki in Batu Tunggal, Asal Mula Tajau Pecah and Beramban, and Andaru. The research method used is descriptive qualitative. The findings reveal that the folk tales packaged in books published by the South Kalimantan Provincial Language Center, Banjarbaru are entitled, Rajang Waki in Batu Tunggal, The Origin of Tajau Pecah and Beramban, and Andaru, each of which has a storyline depicted in each the title of the folk tale. The folklore of Rajang Waki in Batu Tunggal, a social and cultural phenomenon is summarized in the name Rajang Waki in Batu Tunggal. The second folk tale of the origin of Tajau Pecah and Beramban, the social phenomenon lies in the brothers who took part in a competition and the characters who stand out. The cultural phenomenon is related to the origin of the name "Tajau Pecah". Andaru's third story, the social phenomenon lies in a natural disaster that resulted in gold nuggets falling to Datu Langkat and his grandson who then used it as a means of payment to Martapura traders. The cultural phenomenon is related to the origins of the names Taluk Pinyangat, Taluk Basar, Taluk Bintang, Taluk Nyiur, Taluk Manggarukut, and Taluk Tajan.Keywords: culture, folklore, phenomena, socialAbstrakFenomena Sosial Budaya dalam Kajian Tiga Cerita Rakyat Kalimantan Selatan. Cerita rakyat di Kalimantan Selatan termasuk dalam bentuk sastra dengan dituturkannya lewat turun temurun melalui perbincangan orang-orang. Penelitian ini bertujuan mendeskripsikan fenomena sosial budaya pada cerita rakyat Kalimantan Selatan dengan kajian sosiologi sastra pada tiga cerita rakyat yaitu: Rajang Waki di Batu Tunggal, Asal Mula Tajau Pecah dan Beramban, dan Andaru. Metode penelitian yang digunakan berupa kualitatif deskriptif. Hasil temuan memaparkan bahwa cerita rakyat yang dikemas di dalam buku diterbitkan oleh Balai Bahasa Provinsi Kalimantan Selatan, Banjarbaru yang berjudul, Rajang Waki di Batu Tunggal, Asal Mula Tajau Pecah dan Beramban, dan Andaru memiliki alur cerita yang tergambar dari masing-masing judul cerita rakyat tersebut. Cerita rakyat Rajang Waki di Batu Tunggal, fenomena sosial dan budayanya terangkum pada penamaan Rajang Waki di Batu Tunggal. Cerita rakyat kedua Asal Mula Tajau Pecah dan Beramban, fenomena sosialnya terletak pada kakak beradik yang mengikuti sayembara dan karakter tokoh yang menonjol. Fenomena budaya berkaitan dengan asal-usul nama “Tajau Pecah”. Cerita ketiga Andaru, fenomena sosialnya terletak pada adanya bencana alam yang berakibat pada jatuhnya bongkahan emas kepada datu lungkat dan cucunya yang kemudian dijadikan alat pembayaran kepada pedagang Martapura. Fenomena budaya berkaitan dengan asal-usul nama Taluk Pinyangat, Taluk Basar, Taluk Bintang, Taluk Nyiur, Taluk Manggarukut, dan Taluk Tajan.Kata kunci: budaya, cerita rakyat, fenomena, sosial